Giant Sigmoid Diverticulum - Estrugo, Roberto; Laviña, Raúl; Laviña, Raúl; Bounous, Mario (Cirugía del Uruguay, 1981)
The authors report on a case of giant sigmoid diverticulum which is a rare complication of diverticu• lar disease of colon and the first to be published in the medica! literature of Uruguay.